RELEVANSI KURIKULUM DAN PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DENGAN TANTANGAN ERA SOCIETY 5.0: The Relevance of the Islamic Religious Education Curriculum and Instruction to the Challenges of the Society 5.0 Era - Ifan Afandy; Agus; Zakiyah Alfaizah; Muhammad Zaironi (STAI Ma'had Aly Al-Hikam Malang, 2026)
Curriculum and instruction are two components of education that must be integrated to achieve desired educational goals. This article discusses the relevance of the Islamic Religious Education (Pendidikan Agama Islam; PAI) curriculum and instruction in the Society 5.0 era, which focuses on human well-being. Based on a qualitative approach, a literature review, and content analysis techniques, the article reaches the following conclusions: First, the PAI curriculum relevant for implementation in the Society 5.0 era is the concentric model. That is, the PAI curriculum is dominant, and PAI instruction is subordinate. Second, PAI instruction in the Society 5.0 era must consider internal factors comprising physiological and psychological aspects, as well as external factors comprising social and non-social environmental aspects. Third, the characteristics of PAI instruction in the Society 5.0 era include: Transformation of Instructional Methods, Redefinition of the Teacher’s Role, Shift in Evaluation Orientation, and Differentiated Instruction. Kurikulum dan pembelajaran adalah dua komponen pendidikan yang harus diintegrasikan untuk mencapai tujuan pendidikan yang diinginkan. Artikel ini membahas relevansi kurikulum dan pembelajaran Pendidikan Agama Islam (PAI) di era Society 5.0 yang berfokus pada kesejahteraan manusia. Berdasarkan pendekatan kualitatif, jenis penelitian studi pustaka, dan teknik analisis isi, artikel sampai pada simpulan: Pertama, kurikulum PAI yang relevan untuk diterapkan di era Society 5.0 adalah model konsentris. Yaitu kurikulum PAI bersifat dominan, dan pembelajaran PAI bersifat subordinat. Kedua, pembelajaran PAI di era Society 5.0 harus mempertimbangkan faktor internal yang terdiri dari aspek fisiologis dan psikologis, serta faktor eksternal yang terdiri dari aspek lingkungan sosial dan non-sosial. Ketiga, karakteristik pembelajaran PAI di era Society 5.0 antara lain: Transformasi Metode Pembelajaran, Redefinisi Peran Guru, Pergeseran Orientasi Evaluasi dan Pembelajaran Berdiferensiasi. Kata Kunci: Era Society 5.0; Kurikulum PAI; Pembelajaran PAI; Pendidikan Agama Islam.